2011
DOI: 10.1523/jneurosci.0013-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Inhibition Promotes Neurological Recovery after Intraventricular Hemorrhage

Abstract: Intraventricular hemorrhage (IVH) results in neural cell-death and white matter injury in premature infants. No therapeutic strategy is currently available against this disorder. Bone-morphogenetic-protein (BMP) signaling suppresses oligodendrocyte development through basic-helix-loop-helix (bHLH) transcription factors and promotes astrocytosis. Therefore, we hypothesized that IVH in premature newborns initiates degeneration and maturation arrest of oligodendrocyte lineage, and that BMP inhibition alleviates h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 45 publications
0
63
0
Order By: Relevance
“…These findings suggest that increased pressure attributable to progressive hydrocephalus after severe IVH might contribute to periventricular white matter injury and demyelination, as evidenced by corpus callosum thinning and reduced MBP expression. 33,34 In addition, the protective effects of MSC transplantation might be attributable, at least in part, to preventing PHH. The improved rotarod tests results at P31 and P32 after MSC transplantation imply that the protective effects might persist into human adolescence.…”
mentioning
confidence: 99%
“…These findings suggest that increased pressure attributable to progressive hydrocephalus after severe IVH might contribute to periventricular white matter injury and demyelination, as evidenced by corpus callosum thinning and reduced MBP expression. 33,34 In addition, the protective effects of MSC transplantation might be attributable, at least in part, to preventing PHH. The improved rotarod tests results at P31 and P32 after MSC transplantation imply that the protective effects might persist into human adolescence.…”
mentioning
confidence: 99%
“…105 This may be dictated by ongoing inflammation in the brain, as evidenced by preclinical studies and postmortem studies in humans with periventricular leukomalacia that shows persistent, diffuse astro-and microgliosis along the periventricular region of the brain. 106,107 Positron emission and postmortem studies in traumatic brain injury have demonstrated activation of microglia in the thalamus several years after injury. 108,109 Persistent activation of microglia has been observed in other neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease, and multiple sclerosis.…”
Section: Therapeutic Window and Clinical Considerationsmentioning
confidence: 99%
“…In oligodendrocytes, it functions in a dual-mode manner by repressing the differentiation inhibitory signals of the BMP-receptor activated Smad1,5,8 activity [178] and activating oligodendrocytes-promoting factors, thus controlling proper myelination in the CNS [38].…”
Section: Astrocytic and Oligodenrocytic Smad Signalling Influences Nementioning
confidence: 99%